Feasibility of inclusion of mustard (Brassica juncea) genotypes in intercropping and sequential cropping systems with sugarcane (Saccharum officinarum) - SHUKLA', S K; PANDEY, M B (The Indian Journal of Agricultural Sciences, 2013)
The field experiment was conducted for 2 consecutive cropping seasons (1994-96 and 1995-97) to study the effect of different genotypes oflndian mustard [Brassica juncea (L.) Czemj & Cosson) as intercrop/sequential crop on yield and quality of sugarcane (Saccharum officinarum L.). Sole autumn cane produced highest number of millable canes (134 500/ha), highest individual cane weight (911.6g) and sugarcane yield (82 tonnes/ha) and these were significantly higher compared to all the other treatments. Intercropping of different genotypes of mustard produced higher number of millable canes, better growth, higher cane yield. cane equivalent yield, commercial cane sugar equivalent and net profit over the sequential cropping system. Juice quality was not significantly affected by the various intercropping/sequential cropping treatments. Intercropping of sugarcane with ’Bio 417’ mustard (I : 1 row) produced highest cane equivalent yield (99.75 tonnes/ha) and net profit (Rs 50 648/ha).